Extraction and characterization of chitin from Leucaena Leucocephala: article / Shareena Shahira Tajul Arus and Noor Harliza Abd Razak - Tajul Arus, Shareena Shahira; Abd Razak, Noor Harliza (2017)
Thermal property characterization of chitin from Leucaena Leucocephala (LL) extraction was obtained by using Thermogravimetric analysis (TGA) and Elemental Analysis. The purposes of this research were to characterize chitin by extraction of LL pods at different length and aging with 6M HCL and 12M of NaOH by using TGA and Elemental Analysis. By using the instruments, the thermal property is determined. The samples are prepared by chemical process, which are demineralization and deproteinization. The prepared samples then were tested for the thermal property by the TGA and Elemental Analysis. For TGA the results showed at old LL (Set 6) has the highest thermal stability. However, for Elemental Analysis, the results showed that the degree of deacetylation for carbon-nitrogen ratio at young LL was the highest because of high protein content.